دراسة حالات قطع الزجاجي الخلفي في مشفى الأسـد الجامعي باللاذقية / استطباب ونتائج في الفترة بين 2004-2007 / - سليمان, يوسف; جلـول, قحطـان; بسيتون, فاطمة (Latakia University Journal -Medical Sciences Series, 2019)
تعتبر جراحة الشبكية من أحدث أشكال الجراحة العينية في مجتمعنا، حيث أجريت الدراسة على 54 مريضاً من مراجعي العيادة العينية في مشفى الأسد الجامعي باللاذقية ممن خضعوا لعمليات قطع زجاجي خلفي عبر المنطقة الملساء (96 عملية على 59 عين) خلال فترة الدراسة ( 2004-2007 ). حيث وزع هؤلاء المرضى في مجموعات وفقاً للسبب، وتمت مراقبة القدرة البصرية وتوضع الشبكية لديهم . حيث تحسنت القدرة البصرية عند 79.661% من المرضى وبقيت الشبكية متوضعة عند 91.526% من المرضى بعد عام على العمل الجراحي مما يؤكد أهمية هذه الجراحة والعمل على تأهيل أكبر عدد ممكن من كوادرنا العاملة في هذا المجال للحصول على أفضل النتائج. Retinal surgery is considered as one of the most modern kinds of eye surgery in our society. This study was carried out on 54 patients who were admitted at the hospital opthalmic clinic at al assad university hospital in latakia. Those patients underwent pars plana vitrectomy (96 operations on 59 eyes) during the period from 2004 to 2007. The patients were divided into two groups according to the reason. Visual aquity and retinal position were supervised. Visual aquity improved in 79.661% of the patients, while the retina remained positioned in 91.526% of the patients after one year of the surgery. This emphasizes the importance of this kind of surgery, and the need to qualify more than number of our surgeons who are working in this field to obtain the best results.